Building Instructor Capacity for Community-Based Renewable Energy Education through Solar Photovoltaic Training and PBL Module Development - Cucuk Wawan Budiyanto; Indah Widiastuti; Danar Susilo Wijayanto; Taufiq Lilo Adi Sucipto; Mohd Shafie Bakar; Mohd Shawal Jadin; Muhamad Nur Azmi Wahyudi; Diefa Nasywa Aedelia; Muhammad Ardenta Putra Sani; Muhammad Kholil; Slamet Kurniawan Fahrurozi (Borneo Research and Education Center, 2026)
The transition toward renewable energy requires not only technological advancement but also human capacity to disseminate renewable energy knowledge in educational and community settings. This community service program aimed to prepare prospective trainers to facilitate renewable energy learning at the Community Learning Centre (PKBM) Banyutowo in Klaten Regency, Indonesia, while supporting SDG 7 on affordable and clean energy and SDG 4 on quality education. The program adopted a training-of-trainers community service approach and was implemented from January to April 2026. Its activities included preparation and partner-needs alignment, a workshop titled “Green Energy and Green Building for Sustainable STEM Education” held at Universitas Sebelas Maret on 9 February 2026, a partner-site visit to PKBM Banyutowo, and a follow-up teaching activity on 15 April 2026. A total of 54 students from engineering education programs participated as prospective trainers. The workshop consisted of solar photovoltaic (PV) concept presentation, solar PV trainer kit demonstration, PV system design and wiring practice, Problem-Based Learning (PBL) module development, and evaluation. Feedback data were obtained from 19 valid participant responses using a 13-item Likert-scale questionnaire, representing a 35.2% response rate. The responses were used descriptively to identify trends in participants’ perceptions of the workshop. The results indicate active participant engagement, positive response trends regarding organization and instructional delivery, and the development of preliminary PBL module concepts. Seven workshop alumni later facilitated solar PV learning for PKBM learners using the same trainer kit. These findings suggest that integrating technical training, hands-on experimentation, and PBL-oriented pedagogy provides a relevant foundation for strengthening renewable energy literacy and prospective trainer capacity in community-based education.